Molecular biology techniques for loss of heterozygosity detection: the glioma example - Tiago D. P. Ramos; Lidia M. F. Amorim (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT In recent years, many oncology institutions have implemented the use of molecular approaches to assess and manage cancer patients. One commonly observed type of genetic alteration in cancer is the loss of heterozygosity (LOH). In the clinical setting, this molecular genetic marker is an important tool for disease prognosis, diagnosis and treatment. For example, the loss of 1p/19q is a classical molecular marker for oligodendroglioma assessment. In addition, this marker is associated with a favorable prognosis and chemosensitivity in oligodendroglial tumors. Interpretation of the clinical significance of molecular markers requires that health professionals and biomedical scientists understand the basic theoretical fundamentals of molecular diagnostic techniques. Although there are different methodologies to assess LOH, including high-performance techniques, this review aims to describe the polymerase chain reaction (PCR)-based LOH assays and fluorescence in situ hybridization (FISH), which are the molecular techniques most used for evaluation of 1p/19q status in pathology laboratories.